Development of a 3D-printed testicular cancer model for testicular examination education - Power, Rebecca; Hearn, Jason; Gillis, Charlie; Harvey, David; French, Christopher; Organ, Michael (Canadian Urological Association Journal, 2020)
Introduction: Testicular cancer is the most commonly diagnosed malignancy in young males. Testicular examination is a noninvasive and inexpensive means of detecting testicular cancer at an early stage. In this project, a set of 3D-printed models was developed to facilitate teaching testicular examination and improving understanding of testicular malignancies among patients and medical learners. Methods: Five scrotum models were designed: a control model with healthy testes, and four models containing a healthy testicle and a testicle with an endophytic mass of varying size. The anatomy, texture, and composition of the 3D-printed models were refined using an iterative process between the design team and urologists. The completed models were assessed by six urologists, two urology nurse practitioners, and 32 medical learners. Participants were asked to inspect and palpate each model, and to provide feedback using a five-point Likert scale. Results: Clinicians reported that the models enabled accurate simulation of a testicular examination involving both healthy and pathologic testes (x̅=4.3±1.0). They agreed that the models would be useful teaching tools for both medical learners (x̅=4.8±0.5) and patients (x̅=4.8±0.7). Following an educational session with the models, medical learners reported improvements in confidence and skill in performing a testicular examination. Conclusions: 3D-printed models can effectively simulate palpation of both healthy and pathologic testes. The developed models have the potential to be a useful adjunct in teaching testicular examination and in demonstrating abnormal findings that require further investigation.